Dialectics of Islamic and Christian Public Sphere in Kediri - Huda, M Thoriqul; Maharani, Adinda; Nuryana, Dina (Proceedings of International Conference on Muslim Society and Thought, 2024)
Islam and Christianity are religions that have been present in Indonesia for centuries, the history of these two religions cannot be separated from the existence of the Indonesian nation. As time goes by, the relationship between these two religions fluctuates (between conflict and harmony), in certain areas Islam becomes dominant, but in other areas Christianity is the dominant religion. National History records that several times Islam and Christianity were involved in religious conflicts. The dialectic of the relationship between the two religions in the public sphere is the key to fluctuations in the relationship between Islam and Christianity, such as what happened in the Kediri area where Islam and Christianity both exist in the public sphere. Therefore, this research attempts to portray the relationship between Islam and Christianity in public spheres by using a qualitative approach in research, while the technique for obtaining data in research uses interview and observation techniques. The research results show that religion's control of public sphere has exceeded formal and informal boundaries as discussed by Jurgen Habermas. These formal and informal boundaries are exceeded in "public values", namely viewing religious teachings in the public sphere based on the principle of beneficial value. This also goes beyond Jurgen Habermas's thinking about "Public Reason" in looking at the formal and informal areas of religion in the public sphere.